Lattice thermal conductivity of UO2 using ab-initio and classical molecular dynamics - Kim, Hyoungchul; Kim, Moo Hwan; Kaviany, Massoud (AMER INST PHYSICS, 2014)
We applied the non-equilibrium ab-initio molecular dynamics and predict the lattice thermal conductivity of the pristine uranium dioxide for up to 2000 K. We also use the equilibrium classical molecular dynamics and heat-current autocorrelation decay theory to decompose the lattice thermal conductivity into acoustic and optical components. The predicted optical phonon transport is temperature independent and small, while the acoustic component follows the Slack relation and is in good agreement with the limited single-crystal experimental results. Considering the phonon grain-boundary and pore scatterings, the effective lattice thermal conductivity is reduced, and we show it is in general agreement with the sintered-powder experimental results. The charge and photon thermal conductivities are also addressed, and we find small roles for electron, surface polaron, and photon in the defect-free structures and for temperatures below 1500 K. (C) 2014 AIP Publishing LLC.
Keywords: URANIUM-DIOXIDE; ELECTRICAL-CONDUCTIVITY; THERMODYNAMIC PROPERTIES; SINGLE-CRYSTAL; IRRADIATED UO2; 1ST PRINCIPLES; HEAT-CAPACITY; SIMULATIONS; OXIDES; DECOMPOSITION